KESIAPAN DAN TANTANGAN GURU SEKOLAH DASAR DALAM MENERAPKAN PEMBELAJARAN PENDIDIKAN PANCASILA BERBASIS INOVASI DIGITAL - Dellentya, Rizky; Rohman, Zainur; Nur Choyyina, Avin; Mujtahidin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of digital technology in education requires elementary school teachers to integrate digital innovations in Pancasila Education learning. However, teachers' readiness to face this transformation still varies and faces various challenges. This study aims to describe the level of teacher readiness and identify challenges in the implementation of digital innovation-based learning. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and closed questionnaires based on Google Form. The research subjects consisted of three elementary school teachers who were selected using the purposive sampling technique. Data analysis was carried out with the Miles and Huberman interactive model through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that teachers' readiness is in the developing category, which is characterized by basic skills in digital literacy, technology-based pedagogy, and the use of digital media, although it is not evenly distributed. The main challenges include limited infrastructure, digital competency gaps, and lack of environmental support. In addition, it was found that there was a significant relationship between teacher readiness and the success of the implementation of digital innovation-based learning, where teachers who are more prepared are able to create more interactive and effective learning. Therefore, it is necessary to continuously improve teachers' competencies and support the education system adequately.